Enantioselective β-Alkylation of Aldehydes through an Organocatalyzed C–C Bond-Scission Reaction - Huang, Huicai; Abbaraju, Santhi; Zhao, John C.-G. (Synlett, 2016)
A novel organocatalyzed C–C bond-scission reaction of saturated aldehydes containing a suitable leaving group at the β-position was used for the in situ formation of iminium intermediates, which were then captured by nucleophiles to achieve a direct enantioselective β-alkylation of aldehydes. Within short reaction times, the corresponding β-alkylated aldehyde products were obtained in high yields (48–87%) and with excellent enantioselectivities (84–98%).
Keywords: bond scission; alkylation; organocatalysis; aldehydes; enantioselectivity